Curcumin effect on Acanthamoeba triangularis encystation under nutrient starvation - Rachasak Boonhok; Suthinee Sangkanu; Suganya Phumjan; Ramita Jongboonjua; Nawarat Sangnopparat; Pattamaporn Kwankaew; Aman Tedasen; Lim, Chooi Ling; Maria de Lourdes Pereira; Mohammed Rahmatullah; Polrat Wilairatana; Christophe Wiart; et al. (Boonhok et al., 2022)
Curcumin is an active compound derived from turmeric, Curcuma longa, and is known for its benefits to human health. The amoebicidal activity of curcumin against Acanthamoeba triangularis was recently discovered. However, a physiological change of intracellular pathways related to A. triangularis encystation mechanism, including autophagy in the surviving amoeba after curcumin treatment, has never been reported. This study aims to investigate the effect of curcumin on the survival of A. triangularis under nutrient starvation and nutrient-rich condition, as well as to evaluate the A. triangularis encystation and a physiological change of Acanthamoeba autophagy at the mRNA level. In this study, A. triangularis amoebas were treated with a sublethal dose of curcumin under nutrient starvation and nutrient-rich condition and the surviving amoebas was investigated. Cysts formation and vacuolization were examined by microscopy and transcriptional expression of autophagy-related genes and other encystation-related genes were evaluated by real-time PCR. A. triangularis cysts were formed under nutrient starvation. However, in the presence of the autophagy inhibitor, 3-methyladenine (3-MA), the percentage of cysts was significantly reduced. Interestingly, in the presence of curcumin, most of the parasites remained in the trophozoite stage in both the starvation and nutrient-rich condition. In vacuolization analysis, the percentage of amoebas with enlarged vacuole was increased upon starvation. However, the percentage was significantly declined in the presence of curcumin and 3-MA. Molecular analysis of A. triangularis autophagy-related (ATG) genes showed that the mRNA expression of the ATG genes, ATG3, ATG8b, ATG12, ATG16, under the starvation with curcumin was at a basal level along the treatment. The results were similar to those of the curcumin-treated amoebas under a nutrient-rich condition, except AcATG16 which increased later. On the other hand, mRNA expression of encystation-related genes, cellulose synthase and serine proteinase, remained unchanged during the first 18 h, but significantly increased at 24 h post treatment. Curcumin inhibits cyst formation in surviving trophozoites, which may result from its effect on mRNA expression of key Acanthamoeba ATG-related genes. However, further investigation into the mechanism of curcumin in A. triangularis trophozoites arrest and its association with autophagy or other encystation-related pathways is needed to support the future use of curcumin.